Destroying arguments and captivating thoughts: Spiritual warfare prayer as global praxis - Marshall, Ruth (Journal of religious and political practice, 2016)
This paper focuses on contemporary charismatic Christian practices of spiritual warfare and its techniques of warfare prayer. The paradigm of "global spiritual warfare" with its apocalyptic visions, violent language and its obsession with enemies, appears as a particularly polemical instance of Christian supersessionism and expansionism. Drawing on material from Nigeria and the United States, I briefly explore two related axes in order to bring to light the centrality of prayer conceived as a form of political praxis. First, the ways in which charismatic Christianity self-consciously and antagonistically constructs itself as a global force. In this global expansion, prayer as an embodied form of inspired speech is central both to the construction of militant subjects and the occupation of public space. Secondly, since the violence of spiritual warriors is mostly effected through their prayers and testimonies, we are led to question the place of an activist, pragmatist, or even performative model of truth for a political problematics of emancipation and democratization.